The challenge of epic : allusive engagement in the Dionysiaca of Nonnus - Shorrock, Robert. (Mnemosyne, Supplements, 2001)
Nonnus once vied with Homer for popularity; today his Dionysiaca languishes in obscurity. The Challenge of Epic offers a literary critical rehabilitation of Nonnus' fifth-century AD poem. It argues that modern neglect stems from a failure to appreciate the central position of allusion in late-antique poetry. Attention first focuses on intertextual allusion. It is argued that the poet draws on a plethora of allusions to the cycle of Greek mythology in order to imbue his specific narrative with a universal significance. Focus then shifts to metapoetic allusion: the way in which Nonnus alludes self-consciously to the process of writing, and develops parallels between himself and his subject, Dionysus. Through an appreciation of Nonnus' alllusive strategies, the modern reader can again engage with the mind-bending challenge of the Dionysiaca .